Step 1 :Set the function equal to zero to find the x-intercepts: \(2x^3 - 2x^2 - 84x = 0\).
Step 2 :Factor out an x: \(x(2x^2 - 2x - 84) = 0\).
Step 3 :Set each factor equal to zero and solve for x to find the x-intercepts: \(x = 0\) and \(2x^2 - 2x - 84 = 0\).
Step 4 :Solving the quadratic equation gives the x-intercepts: \(x = -6, 0, 7\).
Step 5 :Substitute x = 0 into the function to find the y-intercept: \(f(0) = 2*0^3 - 2*0^2 - 84*0 = 0\).
Step 6 :So, the y-intercept is \(y = 0\).
Step 7 :Final Answer: The x-intercepts are \(x = -6, 0, 7\) and the y-intercept is \(y = 0\). So, the final answer is \(\boxed{-6, 0, 7, 0}\).